EFEKTIVITAS BERBAGAI BAHAN FORMULA PUPUK HAYATI SIANOBAKTERI TERHADAP PERTUMBUHAN DAN HASIL PADI GOGO VARIETAS SITU BAGENDIT - Wahyu Satria Eginarta; Yulia Nuraini; Jati Purwani (Jurnal Tanah dan Sumberdaya Lahan, 2021)
Rice is an important commodity in human life where its production increase must be followed by environmental sustainability and land health. The achievement of increased rice production supported by environmental sustainability can be achieved by utilizing biological fertilizers. One of the microbes that can be used as nutrient providers for rice plants is cyanobacteria. This study was carried out in a greenhouse and soil biology laboratory of the Indonesian Soil Research Institute using a randomized block design with four replications. The treatments tested consisted of F0 (without treatment), F1 (wet cyanobacteria isolate), F2 (dry cyanobacteria isolate), F3 (cyanobacteria + rock phosphate), F4 (cyanobacteria + biochar), F5 (cyanobacteria + kaolin), F6 (cyanobacteria + rock phosphate + kaolin), F7 (cyanobacteria + rock phosphate + biochar), F8 (cyanobacteria + kaolin + biochar). The results showed that the cyanobacteria formula treatment with biochar (F4) carriers showed the highest total population in the parameters of the cyanobacteria population, bacteria, and fungi so that the interaction was said to be positive. The application of cyanobacteria formula to soil chemistry did not significantly affect the post-harvest soil N, P, and K, while the increase in soil pH occurred in the overall treatment of the cyanobacteria formula. Treatment of cyanobacteria formula with biochar carrier (F4) had significantly different results on parameters of number of tillers, number of panicles, grain weight, number of grains.